A New LC-MS/MS Method for Simultaneous and Quantitative Detection of Bisphenol-A and Steroids in Target Tissues: A Power Tool to Characterize the Interference of Bisphenol-A Exposure on Steroid Levels - Errico, Sonia (Molecules, 2019)
Bisphenol A (BPA), an endocrine disruptor, may affect in situ steroidogenesis and alter steroids levels. The present work proposes a liquid chromatography tandem mass spectrometry method to simultaneously quantify BPA, 17β-Estradiol and testosterone in two target tissues: testis and visceral fat mass. Analytes were isolated and lipophilic impurities removed by two serial steps: liquid-liquid and solid phase extraction. All compounds were separated in a single gradient run by Kinetex F5 column and detected via multiple reaction monitoring using a triple quadrupole with a TurboIon electrospray source in both negative and positive modes. The method is selective and very sensitive. In the investigated concentration range, the linearity of the detector response is verified in both tissues. The use of specific SPE cartridges for affinity chromatography purification allows obtaining high percentages of process efficiency (68.0–83.3% for testicular tissue; 63.7–70.7% for visceral fat mass). Good repeatability and reproducibility was observed. The validated method can be efficiently applied for direct biological monitoring in testis and visceral fat mass from mice exposed to BPA. The quantification of compounds in a single assay could be achieved without a loss of sensitivity.